Perancangan Animasi sebagai Media Edukasi Kesadaran Masyarakat terhadap Kasus Penipuan File APK - Fassa, Nikkolas; Aryani, Dewi Isma; Wianto, Elizabeth (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Cybercrime is a brand-new category of crime that involves computer and other technology-based communication networks. In December 2022, a brand-new type of cybercrime surfaced that conned its victims by exploiting APK files. Cybercriminals trick their victims by posing as important individuals as PLN officers, police officers, parcel couriers, family members who send invitation letters, and so forth. When a victim installs a specific program, cybercriminals can steal personal information and even withdraw savings balances from the victim's account by using the private message feature and convincing messages. This study seeks to inform the general population, particularly at-risk demographics between the ages of 40 to 60. The outcomes of data gathering and analysis were based on reviews from chosen respondents in interviews, surveys, and literature reviews. The target audience may easily comprehend the design visualization because it is a straightforward flat vector illustration. Therefore, it can be stated that this educational cartoon can be utilized to educate the public about the several types of cybercrime that exist in the modern period.